ダイ 22 ジ ナンキョク チイキ カンソク タイ キショウ ブモン ホウコク ショ 1981 - 手塚, 正一; テヅカ, マサイチ; 佐藤, 元保; サトウ, モトヤス; 佐久間, 喜代志; サクマ, キヨシ; 馬淵, 和雄; マブチ, カズオ; Tezuka, Masaichi; Satoh, Motoyasu; Sakuma, Kiyoshi; Mabuchi, Kazuo (1986)
P(論文) この報告は第22次日本南極地域観測越冬隊気象部門が, 1981年2月1日から1982年1月31日まで昭和基地において行った, 主として地上および高層気象観測の結果をまとめたものである。地上および高層気象観測は, 総合自動気象観測装置(AMOS)全体を初めて使用し, 観測・統計の自動処理を行ったが, ディスク装置が9月に故障したことにより, 以後の高層気象観測は第20次観測隊までと同じ方法で行った。その他の観測方法, 結果の取り扱いなどは, ほぼ第21次観測隊と同じである。設備については, 新型百葉箱およびCVCFの新設を行った。なお, この報告には高層気象観測資料のスペクトル解析を試みたものも示した。 This paper describes the results of meteorological observations (mainly surface and aerological) carried out by meteorological observation members of the 22nd Japanese Antarctic Research Expedition (JARE-22) at Syowa Station for the period from 1 February 1981 to 31 January 1982. The observations and the statistics of surface and aerological data were automatically processed by using the whole of the Automated Meteorological Observation System (AMOS) for the first time. But trouble occurred in disk equipment of the system in September 1981. Since then, the upper air observations had to be made in the same ways as until JARE-20. The methods of the other observations and statistics of data were almost the same as JARE-21. Concerning the equipment, a new type instrument screen and CVCF (Constant Voltage & Constant Frequency) were installed. This paper also describes the results of the experiment of spectral analysis of the upper air observations. departmental bulletin paper